Pegylated Liposomal Doxorubicin-Induced Acute Transient Encephalopathy in a Patient with Breast Cancer: A Case Report - Michelle Baker (Case Reports in Oncology, 2014)
Background: Pegylated liposomal doxorubicin (PLD) has a unique pharmacokinetic profile and is widely used to treat a variety of malignancies, alone or in combination with other agents. Case Report: A 57-year-old female patient with metastatic breast cancer developed dural metastases to the brain and underwent craniotomy and whole-brain radiation. She continued to receive chemotherapy with carboplatin without any serious complications. Four months later, there was evidence of progression leading to the institution of PLD. During the first course of PLD, there was evidence of acute encephalopathy which resolved after 18 h with discontinuation of this agent. Interestingly, she did well when she was rechallenged with conventional doxorubicin in the following cycles. Conclusion: We hereby report, to the best of our knowledge, the first case of acute transient encephalopathy induced by PLD. We postulate that partial disruption of the blood-brain barrier may have been responsible for PLD-induced encephalopathy.